Exploring the antecedents of trust in electronic word-of-mouth platform: The perspective on gratification and positive emotion - Xie, Xuemei; Liu, Luyao (Frontiers in Psychology, 2022)
With the rapid growth in user generated content (UGC) and social media users, the proclivity for online reviews via the electronic word-of-mouth (e-wom) platform cannot be overlooked. In the context of frequent human-media interaction, trust is acknowledged as an ongoing challenge. As a result, it is critical to increase user trust in the e-wom platform. However, there is a scarcity of research on the antecedents and formation of trust on the e-wom platform. To fill this research gap, this study develops an integrated model to explore the impacts of different gratifications and positive emotion on platform trust, combining uses and gratifications (U&G) theory and stimulus-organism-response (S-O-R) theory. Data was acquired from 268 e-wom users in China using a questionnaire survey, and the structural equation model was used to further analyzes the results. The results show that positive emotion has a positive impact on platform trust. Social gratification (sense of social belonging and sense of self-esteem) positively has a positive impact on positive emotion. Information gratification (information quality) and technology gratification (privacy protection) have a positive impact on social gratification. The results further broaden the scope of trust in human-media interaction research and highlight the psychological mechanisms that underpin platform trust.